Optimal response criteria for the human CRH test in the differential diagnosis of ACTH-dependent Cushing's syndrome. - Newell-Price, J; Morris, D; Drake, WM; Korbonits, M; Monson, J; Besser, G; Grossman, AB (2002)
The CRH test is in widespread use for the differential diagnosis of ACTH-dependent Cushing's syndrome (CS). Despite the greater availability worldwide of human-sequence CRH (hCRH), there are no large series reporting the response criteria that best discriminate between Cushing's disease (CD) and the ectopic ACTH syndrome (EC) when using hCRH, rather than ovine-sequence CRH. We have, therefore, analyzed retrospectively the serum cortisol and plasma ACTH responses to hCRH in patients with ACTH-dependent CS, to develop response criteria that best discriminate between CD and EC. One hundred fifteen consecutive patients with proven ACTH-dependent CS were studied: 101 with CD (78 females; mean age, 40 yr; range, 10-73) and 14 with EC (7 females; mean age, 46 yr; range, 32-69). The response to hCRH was also studied in 30 normal volunteers (NVs; mean age, 29 yr; range, 20-44) with no clinical evidence of CS, and the results were compared. Following basal sampling at -15 and 0 min, hCRH (100 microg iv) was administered via an indwelling forearm cannula at 0900 h and serum cortisol and ACTH were measured at 15-min intervals for 2 h. The mean basal, peak, incremental, and percentage change in the serum cortisol and ACTH at all time points, and combination of time points, were calculated and analyzed to establish the best criteria to discriminate between CD and EC, and also between CD and NVs. The mean serum cortisol concentration in samples obtained at 15 and 30 min after CRH increased by at least 14% above the mean basal in 85 of 100 patients with CD, but in none with EC, giving a sensitivity of 85% at a specificity set at 100%. In contrast, the best plasma ACTH response of a rise of 105%, calculated from the maximal rise, gave only 70% sensitivity at 100% specificity. In the NVs, the maximum cortisol at the mean 15+30 min time point was 615 nmol/liter. Using the 15 and 30 min time points as the reference point, 71 of 100 patients with CD had a rise of serum cortisol greater than 14% and also showed an absolute cortisol level more than 615 nmol/liter. Serum cortisol responses to hCRH can be used to suggest the diagnosis of CD in the majority of patients with this condition, but it should only be used in conjunction with other biochemical and imaging modalities in establishing this important diagnosis. The measurement of plasma ACTH was less helpful in making this distinction, although it may have additional value in excluding ACTH-independent causes of CS. Although we believe that bilateral inferior petrosal sinus sampling remains the single most useful test in discriminating CD from EC in patients with ACTH-dependent CS, hCRH offers rapid diagnostic information and is a useful adjunctive test in establishing the presence of a possible ectopic source.